The role of TNF-alpha in fever: opposing actions of human and murine TNF-alpha and interactions with IL-beta in the rat. - Stefferl, A. (1996)
1. The role of tumour necrosis factor-alpha (TNF-alpha) in fever is controversial. Some studies have indicated that TNF-alpha acts as a cryogen to inhibit fever, while others suggest that TNF-alpha is an endogenous pyrogen which mediates fever. The majority of studies in experimental animals supporting a cryogenic action have been conducted using human (h)TNF-alpha, which has been shown to bind only to one (p55) of the two TNF-alpha receptors in rodents. 2. The aim of the present investigation was to study the role of TNF-alpha in fever by comparing effects of hTNF-alpha, which binds only to the p55 receptor, with those of murine (m) TNF-alpha, which binds to both p55 and p75 TNF-alpha receptors, and to investigate the relationship between TNF-alpha and interleukin-1 (IL-1), an important endogenous pyrogen. 3. Injection of hTNF-alpha (0.3-10 micrograms kg-1, i.p.) had no effect on core temperature in conscious rats (measured by remote radiotelemetry), whereas mTNF-alpha (3 micrograms kg-1) induced fever which was maximal 1 h after the injection (38.2 +/- 0.2 degrees C compared to 37.3 +/- 0.1 degrees C in controls). Intracerebroventricular (i.c.v.) administration of either form of TNF-alpha elicited dose-dependent fever at doses higher than 0.12 microgram kg-1. 4. Peripheral injection of hIL-1 beta (1 microgram kg-1) resulted in fever (38.3 +/- 0.2 degree C compared to 37.2 +/- 0.1 degrees C in controls at 2 h), which was significantly attenuated (P < 0.01) by co-administration of a sub-pyrogenic dose of hTNF-alpha (1 microgram kg-1), but was unaffected by co-administration of mTNF-alpha (0.1 or 0.3 microgram kg-1, i.p.). In contrast, intracerebroventricular (i.c.v.) co-administration of a sub-pyrogenic dose (0.12 microgram kg-1) of hTNF-alpha did not attenuate fever induced by intraperitoneal (i.p.) injection of IL-1 beta, and sub-pyrogenic dose (0.12 microgram kg-1, i.c.v.) of mTNF-alpha significantly prolonged the febrile response to IL-1 beta. Pretreatment of animals with anti-TNF-alpha antiserum (i.c.v.) did not affect the febrile response to systemic IL-1 beta. 5. Animals injected i.p. with a pyrogenic dose of mTNF-alpha developed fever (38.2 +/- 0.2 degrees C compared to 37.3 +/- 0.1 degrees C in controls 2 h after the injection) that was completely abolished by peripheral administration of IL-1ra (2 mg kg-1, P < 0.001), while i.c.v. administration of IL-1ra (400 micrograms/rat) did not affect mTNF-alpha-induced fever. 6. These data indicate that endogenous TNF-alpha is probably a pyrogen and that previous results suggesting cryogenic actions of TNF-alpha resulted from the use of a heterologous protein in the rat. The markedly contrasting effects of mTNF-alpha and TNF-alpha could result from different interactions with the two TNF-alpha receptor subtypes. The data also suggest that fever induced by exogenous TNF-alpha is mediated via release of IL-1 beta in peripheral tissues, but not in the brain.